The characteristics of intersitial lung disease patients attending Groote Schuur Hospital Respiratory clinic - Soin, Gurveen (Department of Medicine, 2024)
Rationale: Interstitial lung diseases (ILDs) encompass a myriad of clinical conditions posing diagnostic challenges in low-income settings. The incidence of Idiopathic pulmonary fibrosis (IPF) is unknown on the African continent. Groote Schuur Hospital (GSH) provides a tertiary referral and follow-up service for patients with suspected ILDs. We set out to determine the burden of IPF and progressive pulmonary fibrosis (PPF) in an African setting. Methods: All patients attending the GSH respiratory clinic with known or suspected ILD were identified over six months. Demographics, spirometry, high-resolution CT findings, histology, and final diagnosis and treatments were captured. IPF incidence was estimated using published population and medical insurance numbers, hospital referral area/pattern, and new IPF diagnoses over a full year period. The presence of PPF was determined by worsening clinical features and lung function in accordance with ATS/ERS guidelines. Results: A total of 103 patients (28 new and 75 follow-ups) were seen over six months. The follow-up patients were predominantly female (81%), diagnosed with systemic sarcoidosis (57%) & connective tissue disease-ILD (CT-ILD) 26%. Hypersensitivity pneumonitis accounted for 5% of follow-up patients, and only 2 IPF patients were in follow-up. CTD-ILD was the most common diagnosis in new patients: 43% and 29% had sarcoidosis. Five new patients were diagnosed with IPF during the 6-month study review and a total of 11 over 1 year. 31% of the CTD-ILD patients had systemic sclerosis SSC; 70% diffuse, and 30% limited. A further 25% had rheumatoid arthritis, and 13% had SLE. Six patients were confirmed to have hypersensitivity pneumonia. Thirteen patients met the criteria for PPF, and a further five patients had rates of decline over four months that, if projected to 12 months, would fulfil the PPF criteria. All 18 patients had an FVC decline of >100mls: mean(range) rate of decline 9.2% (5–22%). Conclusions: Specialised resources and diagnostic modalities to identify and manage ILD patients are required in low resourced settings. The burden of IPF is low but requires confirmation and is likely an underestimate. The potential need for anti-fibrotic treatment is impacted upon by the definition of FVC decline over 12 months.